Relative age and dropout in French male soccer - Delorme, N.; Boiche, J.; Raspaud, M. (Journal of Sports Sciences, 2010)
The aim of this study was to examine the birthdates distribution of French male soccer players (n = 363,590) who dropped out during or after the 2006-2007 season, to determine whether the relative age effect is linked to dropout behaviour. An over-representation of players born late in the competitive year was observed among dropouts, from the U-9 to the U-18 age categories, whereas their counterparts born earlier in the year were under-represented. The distortion of the distribution was most marked for the extreme quarters of the competitive year, and in the U-13 and U-15 categories. This biased distribution was not confirmed for the U-7 category. Finally, regarding the adult category, an unbiased distribution of dropouts was observed as hypothesized. Practical implications to avoid the negative consequences of the relative age effect are advanced.